The Chains Of Transmission Of Syeikh Muhammad Mahfudz At-Tirmasi In Kifayat Al-Mustafid - Abdul Malik Ghozali (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2018)
Past-historical concepts could influence and even led the growth of culture, nation, or individual life. It could be also used as a role-model. The same case occured with the process of Islamic recruitment that occurred at the local level, which was written on the manuscript (lontaraq) in details. Manuscript became the entry point in this study. The focus of the study, in addition, was religious and countries which could be paired together in the structure of kingdom or government agencies. The main source of this study was generated from the Lontaraq Akkarungeng manuscript, and further compared with other Lontaraq or manuscripts. The proposed problem in this study was how the acceptance and the role of the state towards religion in institutional management? The results of the study suggested that the Islamization process by institution effected the management of government agencies. One of them was pararara saraq [syarak/shari’a] that had its own formal structure. It should be noted that the functions of the royal institution was to regulate the socio-culture, statehood, law and etc, consisting of elements of culture (adeq), jurisprudence, speech, social coating (wariq) as the original elements, followed by the elements of Islam in the Islamization phase in Bugis tribe, particularly in regency of Wajo. The Islamic element was then integrated into one value, which could be further integrated with the national legal system. Keywords: Religion, Islamization, Lontaraq, Institution, Wajo.